Challenges in academic performance among nursing students during flood disasters at a University in Dagupan City - Jordan Llego; Princess Erika Permison; Nicole Imbuido; Mikaella Concepcion; Lara Jane Caneja; Francine Joy Zaulda (Science Talks)
Background: Disasters, both natural and human-made, universally affect communities and are recognized as major environmental and global challenges. Aim: This study seeks to investigate the specific academic challenges faced by nursing students during flood disasters at a university in Dagupan City. It also seeks to compare the academic performance of these students during and after the flood season. Design: Descriptive-comparative study. Settings: A private university in Dagupan City, known for its flooding susceptibility, hosted the study. Participants: A total of 236 nursing students participated in the study. Methods: For data collection, the study adopted a total enumeration approach, categorizing the data into archived and survey categories. The study utilized descriptive statistics like frequency, percentage, mean, and standard deviation. Paired sample t-tests were conducted to evaluate differences in academic performance during and after the flood. Results: Flood-related disruptions, including class suspensions and academic difficulties, affected many nursing students. The floods led to reduced study hours, unavoidable absences, and health risks, all of which detrimentally impacted their academic achievements. Additionally, transportation disruptions significantly hindered educational activities. After the disaster, the students' academic performance improved noticeably. Conclusions: Flooding profoundly affects the educational journey of nursing students, impairing both their academic outcomes and overall health. Despite these challenges, the students demonstrated remarkable resilience by improving their academic performance post-disaster. This improvement underscores the importance of robust support systems, including disaster-related health education and flexible academic policies to manage unexpected disruptions. The observed post-flood academic recovery attests to the effectiveness of educational institutions' rehabilitation and support strategies.